Review of the marketing strategies proposed as solutions to the depression of ERP market - (:unkn) unknown (International Business Information Management Association, IBIMA, 2005)
The main object of this paper is to review the marketing strategies, which are proposed by consultant firms as solutions to the depression of ERP Market. The competition in Industrial Enterprise Applications (IEA) market became fierce in recent years, since annual revenues of vendors decreased drastically after the expansion of sales due to Y2K problem. Counselor companies suggest some strategies such as marketing new IEA products and aiming to the mid-sized companies. Some of them also propose that Enterprise Resource Planning (ERP) market revive soon with the need of upgrading old technology ERP systems. A field study is conducted with 68 respondent companies, which had installed ERP system in Turkey. The profiles of old ERP customers are used to evaluate these strategies. This paper proposes an information base to ERP vendors, which want to understand the needs and attributes of their customers, and improve their services. Findings of this research validate the trends predicted by adviser companies.